On design-based empirical research and its interpretation and ethics in sustainability science - Barrett, Christopher B. (Proc Natl Acad Sci U S A, 2021)
Generating credible answers to key policy questions is crucial but difficult in most coupled human and natural systems because complex feedback mechanisms can confound identification of the causal mechanisms behind observed phenomena. By using explicit research designs intended to isolate the causal effects of specific interventions on community monitoring of common property resources, and on the well-being of those resources and their human neighbors, the papers in this Special Feature offer an important advance in empirical sustainability science research. Like earlier advances in my own field of development economics, however, they suffer some avoidable interpretive and ethical errors. This essay celebrates the powerful potential of design-based sustainability science studies, much of it admirably reflected in this set of papers, while simultaneously flagging opportunities to improve future work in this tradition.